Reinstatement of Athis miastagma (Dyar, 1925) (Lepidoptera: Castniidae) as a valid species inhabiting the Pacific slope of Central Mexico - González, Jorge M.; López G., Bernardo; Díaz, José De Jesús García; Simon, Sabrina; Monteys, Víctor Sarto I; Worthy, Robert (Zootaxa, 2021)
Mexico is the Mesoamerican country with the highest number of Castniidae species (12), most of which are found in the dry regions of the country. Among these, Athis hechtiae (Dyar, 1910) was considered a species widely distributed in Mexico after Athis miastagma (Dyar, 1925) was synonymized with A. hechtiae over two decades ago. A genetic and morphological study, as well as details of the natural history of various populations of these two taxa have led us to restore Athis miastagma as a valid species (stat. rest.), increasing the number of castniids recorded in Mexico to 13.